2021
DOI: 10.1242/dev.199384
|View full text |Cite
|
Sign up to set email alerts
|

longfin causes cis-ectopic expression of the kcnh2a ether-a-go-go K+ channel to autonomously prolong fin outgrowth

Abstract: Organs stop growing to achieve a characteristic size and shape in scale with the body of an animal. Likewise, regenerating organs sense injury extents to instruct appropriate replacement growth. Fish fins exemplify both phenomena through their tremendous diversity of form and remarkably robust regeneration. The classic zebrafish mutant longfint2 develops and regenerates dramatically elongated fins and underlying ray skeleton. We show longfint2 chromosome 2 overexpresses the ether-a-go-go-related voltage-gated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Recently, we demonstrated that the ectopic expression of the kcnj13 gene in zebrafish somites could lead to elongated fins in zebrafish 23 . Additionally, kcnk5 , slc12a7a , and knnh2a mutant zebrafish develop long fins in zebrafish 46‐48 . Thus, the temporal and transient kir genes' expression could be a cellular bioelectric signal for developmental patternings, such as seen in the ectopic somite gene expression of kcnj13 in our long‐fin mutant Dhi2059.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, we demonstrated that the ectopic expression of the kcnj13 gene in zebrafish somites could lead to elongated fins in zebrafish 23 . Additionally, kcnk5 , slc12a7a , and knnh2a mutant zebrafish develop long fins in zebrafish 46‐48 . Thus, the temporal and transient kir genes' expression could be a cellular bioelectric signal for developmental patternings, such as seen in the ectopic somite gene expression of kcnj13 in our long‐fin mutant Dhi2059.…”
Section: Discussionmentioning
confidence: 71%
“…23 Additionally, kcnk5, slc12a7a, and knnh2a mutant zebrafish develop long fins in zebrafish. [46][47][48] Thus, the temporal and transient kir genes' expression could be a cellular bioelectric signal for developmental patternings, such as seen in the ectopic somite gene expression of kcnj13 in our long-fin mutant Dhi2059. It is reasonable to speculate that the somite expression of kcnj2a, kcnj11, kcnj5, and other K+ channels (eg, KCa) 49 could be part of a general endogenous fin patterning regulation system for zebrafish fins.…”
Section: Bioelectricity and Developmental Patterningmentioning
confidence: 99%
“…The smg8 protein acts as a regulator of kinase activity involved in nonsense-mediated decay of mRNAs ( 35 ) and is an unlikely candidate of the long-fin phenotype. In contrast, kcnj15 encodes a potassium channel, which is a much better candidate, as several genes encoding potassium channels, including kcnk5b ( 36 ), kcnh2a ( 37 ), kcnj13 ( 38 ), and kcc4a ( 39 ), have been identified to cause various long-fin phenotypes in zebrafish. Moreover, when comparing the expression profiles of the two candidate genes in caudal fin between long-fin and short-fin individuals by RNA sequencing (RNA-seq), we found that the expression levels of smg8 were similar between different fish groups, while kcnj15 showed a significant difference as it is highly expressed in long-fin breeds ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The causal mutant gene of the lof has remained unknown for decades until recently. Two independent reports pinpointed Kcnh2a, a voltage-gated potassium channel [ 105 , 106 ]. There is a 0.9 Mb chromosomal reversion upstream of the kcnh2a gene on chromosome 2 [ 106 ].…”
Section: Bioelectricity Evidence From Zebrafish Geneticsmentioning
confidence: 99%